Case Report: Calcium sensing receptor gene gain of function mutations: a case series and report of 2 novel mutations - Ali, Dalal S.; Marini, Francesca; Alsarraf, Farah; Alalwani, Hatim; Alamri, Abdulrahman; Khan, Aliya A.; Brandi, Maria Luisa (Frontiers in Endocrinology, 2023)
Autosomal dominant hypocalcemia (ADH1) is a genetic disorder characterized by low serum calcium, and low or inappropriately normal levels of parathyroid hormone.The disease is caused by a heterozygous activating mutation of the calcium-sensing receptor (CaSR) gene, encoding a G-Protein-coupled cell membrane sensor of extracellular calcium concentration mainly expressed by parathyroid glands, renal tubules, and the brain. ADH1 has been linked to 113 unique germline mutations, of which nearly 96% are missense mutations. There is often lack of a clear genotype/phenotype correlation in the reported literature.Here, we described a case series of 6 unrelated ADH1 probands, each one bearing a gain-of-function CaSR mutation, and two children of one of these cases, matching our identified mutations to the same ones previously reported in the literature, and comparing the clinical and biochemical characteristics, as well as the complication profile. As a result of these genetic and clinical comparisons, we propose that a genotype/phenotype correlation may exist because our cases showed similar presentation, characteristics, and severity, with respect to published cases with the same or similar mutations. We also contend that the severity of the presentation is highly influenced by the specific CaSR variant. These findings, however, require further evaluation and assessment with a systematic review.